TECHNICAL AND ECONOMIC COMPARISON OF WASTEWATER SLUDGE PRETREATMENT BEFORE ANAEROBIC DIGESTION - Бойченко, С. В. (Science-based technologies, 2016)
In this article the problem of disposal and recycling of wastewater sludges was considered. The existing sewage treatment plant of Boryspil International Airport is characterized. Based on the researches, the most effective methods of pre-treatment of household wastewater sludges that affecting at the intensity of hydrolysis during anaerobic digestion was analyzed. The basic requirements for technological processes of digestion of wastewater sludges from aviation enterprise on the hydrolysis stage of organic compounds was presented. The analysis of technical and economic comparison results of selected variants of wastewater sludge pretreatment was performed. Based on the results of a technical and economic comparison, the performance criterion of specific method of sludge pretreatment was introduced. On this basis, it was formed conclusions regarding the usefulness of a technologies of wastewater sludges pretreatment from aviation enterprise.